Forecasting hazardous and adverse weather in the Middle Urals using hydrodynamic atmosphere models - A.V. Bykov; N.A. Kalinin; E.V. Pishchal'nikova; A.N. Shikhov (Учёные записки Казанского университета: Серия Естественные науки)
The problem of verification of short-term numerical forecast of hazardous and adverse weather using the WRF mesoscale atmosphere model for the territory of the Middle Urals has been considered. The meteorological situations associated with the intense precipitation and convection development in Perm krai and Sverdlovsk oblast (Russia) in 2016 have been studied. The success of heavy snow forecast has been assessed by comparison with the data from weather stations. To forecast heavy snow, data from the GFS and GEM global models have been used along with the WRF model. The comparison with data from the WRF model has demonstrated that the GEM model provides the most accurate forecast. The forecasts of convective phenomena have been assessed with the help of the object-oriented approach based on the comparison of the real and forecasted positions of mesoscale convection-allowing systems. In a number of cases, the WRF model is able to forecast the place and time of adverse weather (including the local ones), which is impossible when the synoptic method is used. The main restriction for numerical forecast of convective hazardous weather is the inability to determine the spatial position of mesoscale convection-allowing systems. Understating the gust velocity of squall winds also occurs, but this problem can be solved by reducing the grid step to 2–3 km.